PERKEMBANGAN KEWENANGAN PERADILAN TATA USAHA NEGARA MENGADILI SENGKETA KEPEGAWAIAN APARATUR SIPIL NEGARA - Enrico Simanjuntak (Jurnal Hukum Peratun, 2021)
The development of personnel law regarding litigation has experienced tremendous development, but some of the latest literature in the field of personnel law is still referring to the mechanism of litigation that is already irrelevant. As is known now after the enactment of the Supreme Court Regulation (Perma) No. 6 of 2018 concerning Government Administration Dispute Resolution Guidelines After Taking Administrative Review, the principle applies so long as it is not determined otherwise by certain sectoral regulations (lex specialis), submitting a claim to the State Administrative Court (PTUN) must first take administrative efforts internally or quasi-judicial institution (lex generalis). As the initial intention of the State Civil Apparatus Act (UU Aparatur Sipil Negara), now the resolution of personnel disputes must be preceded by internal administrative review before being submitted to the State Administrative Court.